2001
DOI: 10.1046/j.1525-139x.2001.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Pass Continuous Flow Peritoneal Dialysis Using Two Catheters

Abstract: With a renewed interest in continuous flow peritoneal dialysis (CFPD), our standard practice of implanting a second catheter in those patients facing access failure provided us the opportunity to perform acute studies on CFPD in these patients, since it temporarily provided us with two catheters. Four patients were studied, with a total of five studies performed. A standard protocol was followed utilizing 1.5% dextrose solution, a 2 L fill, an inflow rate of 200 ml/min with a proportionate outflow for a 4-hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 6 publications
3
20
0
Order By: Relevance
“…Continuous flow peritoneal dialysis has been shown in chronic adult PD patients to increase the clearance of small solutes 3-to 8-fold and to significantly increase ultrafiltration compared to conventional PD (100)(101)(102). In one of the few studies of this dialysis technique in patients with AKI, Ponce et al used CFPD in two adult AKI patients and achieved a clearance similar to that reported with extracorporeal blood purification methods and an ultrafiltration rate of 200 -500 mL/h (45).…”
Section: Rationalementioning
confidence: 99%
See 3 more Smart Citations
“…Continuous flow peritoneal dialysis has been shown in chronic adult PD patients to increase the clearance of small solutes 3-to 8-fold and to significantly increase ultrafiltration compared to conventional PD (100)(101)(102). In one of the few studies of this dialysis technique in patients with AKI, Ponce et al used CFPD in two adult AKI patients and achieved a clearance similar to that reported with extracorporeal blood purification methods and an ultrafiltration rate of 200 -500 mL/h (45).…”
Section: Rationalementioning
confidence: 99%
“…5 PDI rate of between 100 -300 mL/min and a glucose concentration of 1.5%. With this prescription, greatly improved ultrafiltration and clearances were obtained (100)(101)(102)(103). However, these studies were conducted with stable chronic PD patients.…”
Section: Rationalementioning
confidence: 99%
See 2 more Smart Citations
“…Conventional modalities of APD using the intermittent technique can almost double the clearances obtained with CAPD. However, CFPD can achieve clearances close to the mass transfer area coefficient for urea or approximately 40 ml/min [11].…”
mentioning
confidence: 98%